SMALL BUSINESS ENTITIES: EXPANDING INNOVATION - Obidkhanov Javakhirkhan Avazkhanovich (Modern American Journals, 2025)
This article examines the importance of small businesses in the development of a green economy. Small businesses play a key role in promoting environmentally sustainable practices, fostering innovation, creating jobs and improving local communities. The introduction of green technologies helps reduce costs, increase competitiveness and attract investment, which contributes to sustainable development.
Keywords: Green economy, innovation, ecology, small business, technology, use, electric transport, environment, technology implementation.